2023
DOI: 10.21037/qims-22-486
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in Scheimpflug corneal densitometry and their correlations with corneal topographic measurements in a healthy Chinese population

Abstract: Background: Objective measurement of corneal densitometry (CD) values can be used to assess corneal transparency and health status, to investigate corneal diseases, and to review anterior segment surgeries.However, literature regarding the association between CD and corneal parameters in healthy adolescent and older individuals is limited. This study investigated age-related changes in Scheimpflug CD values and their correlations with age, sex, and corneal topographic parameters.Methods: This retrospective cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…We found in our study that there was no correlation between CD of all zones in all layers and central corneal thickness postoperatively. It was indicated by previous studies that CD was positively correlated with central corneal thickness in high myopic and keratoconus eyes [2,16] , but showed no correlation in normal eyes [17] , which is consistent with our findings. Ishikawa et al [18] reported a positive correlation between CD values and postoperative corneal thickness after cataract surgery, indicating that corneal edema undetectable by slit-lamp could be evaluated with CD measurement, which also proved the importance of CD examinations in follow-up visits after corneal surgeries.…”
Section: Discussionsupporting
confidence: 93%
“…We found in our study that there was no correlation between CD of all zones in all layers and central corneal thickness postoperatively. It was indicated by previous studies that CD was positively correlated with central corneal thickness in high myopic and keratoconus eyes [2,16] , but showed no correlation in normal eyes [17] , which is consistent with our findings. Ishikawa et al [18] reported a positive correlation between CD values and postoperative corneal thickness after cataract surgery, indicating that corneal edema undetectable by slit-lamp could be evaluated with CD measurement, which also proved the importance of CD examinations in follow-up visits after corneal surgeries.…”
Section: Discussionsupporting
confidence: 93%
“…Scheimpflug corneal densitometry is a quantitative measure of corneal transparency, and its value increases with age ( 20 ). One study ( 21 ) reported that central anterior corneal densitometry values were significantly higher in silicone hydrogel contact lens wearers than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] The alterations in CD values after 7 years post SMILE is distinct from the age-related variations observed in healthy corneas. [ 21 22 ] There are two potential reasons for this contrasting pattern. Firstly, it is important to note that our subjects, with an average age of 30.5 ± 8.6 years, were monitored longitudinally for 7 years, which contrasts with the prior research that concentrated on CD value shifts in 10-year intervals related to aging.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it is important to note that our subjects, with an average age of 30.5 ± 8.6 years, were monitored longitudinally for 7 years, which contrasts with the prior research that concentrated on CD value shifts in 10-year intervals related to aging. [ 21 22 ] Furthermore, stromal thinning that occurs from SMILE may lead to a decrease in corneal cell and basal nerve density. [ 23 ] Consequently, a more precise assessment of posterior backscattering could be made, potentially resulting in reduced CD values.…”
Section: Discussionmentioning
confidence: 99%